Tissue engineered cartilage with different human chondrocyte sources: articular, auricular and nasal septum - Idrus, Ruszymah; Chua, Kien Hui; Sha'ban, Munirah; Ahmad Noruddin, Nur Adelina; Saim, Aminuddin (Islamic World Academy of Sciences, 2005)
Tissue engineering is a new biotechnological field that has emerged recently, providing an alternative to the treatment of damages and defects of human tissues. Amongst the most researched tissues is cartilage. In this study, the general characteristics of chondrocytes derived from three different sources in the body: articular, auricular and nasal septum cartilage, were investigated, looking both at cellular and tissue construct levels. With the approval of Research and Ethical Committee of Medical Faculty, Universiti Kebangsaan Malaysia, redundant cartilages from human articular, auricular and nasal septum were obtained from several patients during surgical procedures. Samples were digested and chondrocytes obtained were cultured in a mixture of Ham's F12 : DMEM medium. All three chondrocyte sources were found to behave quite similarly in terms of cell morphology, gene expressions and histological analysis. No significant difference of the growth rates was shown by the three chondrocyte sources. Histological analysis via H and E and Safranin O stainings of the tissue-engineered cartilages demonstrate resemblance to the native cartilage. Gene expression results showed that collagen type II expression reduces after every passage, and collagen type I gene is expressed as early as P0, however, there were re-expressions of Collagen Type II gene in the in vivo construct. We have successfully engineered cartilage tissues which are similar to the native cartilage, using sources from articular, auricular and nasal septum chondrocytes.